Studies in the Sermon on the Mount ; v.1 - Lloyd-Jones, David Martyn, 1899-1991. (London, UK IVF, 1959)
Contents : v.1 : Matthew chapter 5
Keywords: Sermon on the Mount -- commentaries; Bible. N.T. Matthew V -- commentaries